Evaluasi Pengelolaan Sampah Menggunakan Climate Resilient and Inclusive Cities (CRIC) Waste Assessment Tool Kota Palembang - Alfansyah, M Audito; Fitriani, Heni; Hadinata, Febrian (Kadiri University, 2024)
Waste is a problem that cannot be ignored because it is always generated in all aspects of life. The Climate Resilient and Inclusive Cities CRIC Waste Assessment Tool helps in analyzing the current situation in the city and provides important and practical recommendations from both technical aspects, governance, and social issues. The research aims to evaluate urban waste management using the Climate Resilient and Inclusive Cities (CRIC) Waste Assessment Tool based on management technology in Palembang City. A quantitative strategy was used in this research, along with a descriptive and verification research method. Secondary data is taken from the national waste management information system and other literature to fill in the CRIC Waste Assessment Tool application. Data analysis using CRIC Tool covers waste management, governance, economy and knowledge of citizens, GHG emissions. The results of measuring waste management performance with CRIC show that waste management in the city is still low, most of the waste is disposed of uncontrollably, resulting in SLCPs. Waste banks and TPS3R are still lacking. Achievement of waste management to reduce greenhouse gas emissions has only reached 50% of the recommended target. Proper waste handling is still lacking, such as reduced dumping, open burning, and better composting practices. This will support modifications in waste handling from the community, which can support waste management technology development.